2023
DOI: 10.1128/mbio.03261-22
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of a Female-Specific Apetala 2 Transcription Factor Blocks Oocyst Shedding in Cryptosporidium parvum

Abstract: The parasite Cryptosporidium infects millions of people worldwide each year, leading to life-threatening diarrheal disease in young children and immunosuppressed individuals. There is no vaccine and only limited treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…4 B ) consistent with Cre-mediated excision. We also noted some leaky Cre activity in the absence of rapamycin as previously described ( 34 ). Infected cultures grown in the presence or absence of rapamycin for 48 h, were fixed and imaged.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…4 B ) consistent with Cre-mediated excision. We also noted some leaky Cre activity in the absence of rapamycin as previously described ( 34 ). Infected cultures grown in the presence or absence of rapamycin for 48 h, were fixed and imaged.…”
Section: Resultssupporting
confidence: 70%
“…We recently demonstrated the use of dimerizable Cre recombinase (DiCre) for rapamycin induced gene ablation; however, introducing loxP sites and recombinase in a single transfection is challenging (see extended technical discussion in ref. 34 ). To overcome this, we devised a model in which we cross a Cre driver and a floxed strain ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The seminal work of English et al (2022) provided insights into the infection kinetics of C. parvum, where it was demonstrated that the parasite must undergo three cycles of asexual replication before sexual development will occur (42). Within the transwell plate, fertilisation is very limited which results in cessation of C. parvum infection after three days post-infection (20,43). The findings of the present work suggest that one cycle of successful sexual replication occurred within the microfluidic device, and excystation of oocysts produced in vitro occurred within the microchannel.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research on ApiAP2 TFs in apicomplexan parasites such as Plasmodium spp., T. gondii, and Cryptosporidium [35][36][37][38][39][40], their function in Eimeria pp. has not been studied to date.…”
Section: Discussionmentioning
confidence: 99%